Modulation of the Gut Microbiota by Krill Oil in Mice Fed a High-Sugar High-Fat Diet - Lu, Chenyang; Sun, Tingting; Li, Yanyan; Zhang, Dijun; Zhou, Jun; Su, Xiurong (Frontiers in Microbiology, 2017)
Multiple lines of evidence suggest that the gut microbiota plays vital roles in metabolic diseases such as hyperlipidemia. Previous studies have confirmed that krill oil can alleviate hyperlipidemia, but the underlying mechanism remains unclear. To discern whether krill oil changes the structure of the gut microbiota during the hyperlipidemia treatment, 72 mice were acclimatized with a standard chow diet for two weeks and then randomly allocated to receive a standard chow diet (control group, n=12) or a high-sugar-high-fat (HSHF) diet supplemented with a low (100 μg/g•d, HSHF+LD group, n=12), moderate (200 μg/g•d, HSHF+MD group, n=12) or high dosage of krill oil (600 μg/g•d, HSHF+HD group, n=12), simvastatin (HSHF+S group, n=12) or saline (HSHF group, n=12) continuously for 12 weeks. The resulting weight gains were attenuated, the liver index and the low-density lipoprotein, total cholesterol and triglyceride concentrations showed a stepwise reduction in the treated groups compared with those of the control group. A dose-dependent modulation of the gut microbiota was observed after treatment with krill oil. Low- and moderate- doses of krill oil increased the similarity between the composition of the HSHF diet-induced gut microbiota and that of the control, whereas the mice fed the high-dose exhibited a unique gut microbiota structure that was different from that of the control and HSHF groups. Sixty-five key operational taxonomic units (OTUs) that responded to the krill oil treatment were identified using redundancy analysis, of which twenty-six OTUs were increased and thirty-nine OTUs were decreased compared with those of the HSHF group. In conclusion, the results obtained in this study suggest that the structural alterations in the gut microbiota induced by krill oil treatment were dose-dependent and associated with the alleviation of hyperlipidemia. Additionally, the high-dose krill oil treatment showed combined effects on the alleviation of hyperlipidemia and obesity.